PELATIHAN DASAR PEMASANGAN PERALATAN INSTALASI LISTRIK UNTUK MENCEGAH KEBAKARAN DI BR. SAMBIAN UNDAGI DS. TIMPAG KEC. KERAMBITAN-TABANAN - Partha, C.G.I.; Wijaya, I.W.A.; Janardana, I.G.N.; Budiastra, I.N.; Frederika, A. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Fire often occurs due to electricity problem. Fire is frequently caused by poor electricity installation, where in most incidences, short circuit is the trigger. Cable is an example of electrical devices that is susceptible to short circuit. Usage of cable that is not compatible with its rule causes the burning of the coating of the cable wrapper. Nowadays, installations of devices that do not satisfy the electricity rule are excessively seen in public places. Insufficient usage of duct tape, usage of plastic to isolate cable, usage of old cable, and usage of electrical socket that is out of its capacity are some issues related to fire triggers. Due to these information, early and good information for society related to fire detection is highly required. To answer the aforementioned problem, we have conducted a public service program. In this program, a training related to the basic of electricity devices installation is given. Through this training, society will care with the risks that are caused by electricity to peoples and environment.